PENGEMBANGAN MEDIA PEMBELAJARAN MICROSOFT OFFICE EXCEL 2003 BERBASIS WEBSITE DENGAN MODEL SOMATIS, AUDITORI, VISUAL DAN INTELEKTUAL (SAVI) PADA MATA PELAJARAN TIK KELAS VIII SEMESTER II DI SMP NEGERI 4 DENPASAR - Maya Stefany, Evy (Universitas Pendidikan Ganesha, 2012)
This is a research aims to (1) design and implement the development of learning media Microsoft Office Excel 2003 based website with a model of somatic, auditory, visual, and intellectual (SAVI) on ICT subjects in the second half of class VIII Junior High School 4 Denpasar, (2) knowing responses of students and teachers of ICT subjects in class VIII Junior High School 4 Denpasar towards the development of learning media Microsoft Office Excel 2003 based Website with a model of somatic, auditory, visual, and intellectual (SAVI). Types of research used in this study is research and development (Research and Development / R & D) with Dick and Carey model of development. The study involved students in grade VIII Junior SMP 4 Denpasar academic year 2011/2012. Data on student learning resource was is obtained by using interviews. The next product tested to the students through three stages, namely the individual trials, small group testing, and field trials. The subjects of this research trial consisted of 3 students for individual trials, 12 students for small group trials, and 35 students for field trials. Data collected in this study are data from the test material experts, expert test design, test media expert learning, and students from the trial. Validity of the learning media as well as student and teacher responses obtained using the questionnaire method. The data obtained were analyzed descriptively. The development of instructional media Microsoft Office Excel 2003 based Website using SAVI learning model suggests that the findings from the content of the material that is expert subject teachers concerned with the achievement of 91.4% is in very good category. The results of the learning media specialists with 92.00% level of achievement is in very good category. The results of the instructional media design experts with the achievement of 90.76% is in very good category. The results of field trials with the achievement of 93.14% is in very good category. Development of instructional media is in a category very well that this is worth learning media used in the study.